Alloys, alloy powders, alloy components, and composite components

A Ni-based alloy with a tailored composition addresses the need for high-temperature hardness and thermal stress resistance in carbide alloys, particularly in additive manufacturing, by forming fine carbide and γ' phases, resulting in improved wear resistance and crack resistance.

JP7670237B2Active Publication Date: 2025-04-30PROTERIAL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024519225
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-02
Filing Date
2023-05-01
Publication Date
2025-04-30
Estimated Expiration
2043-05-01

AI Technical Summary

Technical Problem

Carbide alloys require high hardness at high temperatures and resistance to cracking due to thermal stress, especially when used in additive manufacturing methods.

Method used

A Ni-based alloy with a specific chemical composition, including Cr, C, Ti, Nb, and Ta, is developed, which provides high hardness at high temperatures and resistance to cracking. The alloy has a ratio of Ti, Nb, and Ta atoms to C atoms greater than 1.5, ensuring the formation of fine carbide phases and γ' phases for improved wear resistance and hardness.

Benefits of technology

The alloy achieves high hardness at elevated temperatures and exhibits high crack resistance, making it suitable for use in additive manufacturing without preheating the substrate, thus reducing thermal stress and preventing cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670237000004
    Figure 0007670237000004
  • Figure 0007670237000005
    Figure 0007670237000005
  • Figure 0007670237000006
    Figure 0007670237000006
Patent Text Reader

Abstract

Provided are an alloy having high hardness at high temperature and having high crack resistance, a powder made from the alloy, and an alloy member and a composite member including the alloy. The alloy contains, in mass%, 10-20% of Cr, 1.0-2.5% of C, 3-8% of Ti, 8-15% of either Nb or Ta, or in total of Nb and Ta, less than 0.5% of B, 2% or less of Al, 8% or less of Mo, and 8% or less of W (the total amount of Mo and W is less than 10%), with the remainder comprising Ni and inevitable impurities, wherein the ratio of the total number of Ti, Nb and Ta atoms to the number of C atoms is greater than 1.5.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alloy, an alloy powder, an alloy part, and a composite part. [Background technology]

[0002] Cemented carbide is used for various applications such as cutting tools, warm and hot forging dies, etc. For example, Patent Document 1 describes a method for manufacturing a cutting tool having a cutting part made of a WC-Co based cemented carbide containing tungsten carbide (WC) and cobalt (Co) as main components.

[0003] Patent Document 2 describes an alloy that is excellent in corrosion resistance and wear resistance, has crack resistance, and is suitable for additive manufacturing methods, etc. The alloy described in Patent Document 2 contains, in mass %, 18-22% Cr, 18-28% Mo, 1.5-57% Ta, 1.0-2.5% C, 0-42% Nb, 0-15% Ti, 0-27% V, 0-29% Zr, with the remainder being Ni and unavoidable impurities, and satisfies the molar ratio of (Ta+0.7Nb+Ti+0.6V+Zr) / C=0.5-1.5. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2017-501890 [Patent Document 2] International Publication No. 2021 / 201118 Summary of the Invention [Problem to be solved by the invention]

[0005] Depending on the application, it may be desirable for the cemented carbide to have high hardness at high temperatures. It is also desirable for the cemented carbide to be easily sculpted by additive manufacturing. In additive manufacturing, a metal material is melted and solidified, which generates large thermal stress. Therefore, it is desirable for the cemented carbide to have high resistance to cracking due to thermal stress. Therefore, the present invention provides an alloy that has high hardness and high cracking resistance at high temperatures even when used in additive manufacturing, for example, and a powder made of this alloy, as well as an alloy part and a composite part containing this alloy. [Means for solving the problem]

[0006] According to a first aspect, In mass%, Cr 10-20%, C 1.0 to 2.5%, Ti 3-8%, Nb and / or Ta, 8 to 15% in total, B is less than 0.5%. Al 2% or less, Mo is 8% or less. Contains 8% or less W, The sum of Mo and W is less than 10%; The balance is Ni and unavoidable impurities. An alloy is provided in which the ratio of the total number of Ti, Nb and Ta atoms to the number of C atoms is greater than 1.5.

[0007] According to a second aspect, In mass%, Cr 10-20%, C 1.0 to 2.5%, Ti 3-8%, Nb and / or Ta, 8 to 15% in total, B is less than 0.5%. Al 2% or less, Mo is 8% or less. Contains 8% or less W, The sum of Mo and W is less than 10%; The balance is Ni and unavoidable impurities. An alloy powder is provided in which the ratio of the total number of Ti, Nb and Ta atoms to the number of C atoms is greater than 1.5.

[0008] According to a third aspect, there is provided an alloy part comprising at least in part the alloy of the first aspect.

[0009] According to a fourth aspect, there is provided a substrate and a laminated alloy layer on a surface of the substrate, A composite component is provided, wherein the alloy layer comprises an alloy of the first aspect.

[0010] According to a fifth aspect, there is provided a method for manufacturing a semiconductor device comprising the steps of: A mold is provided, wherein the alloy layer comprises an alloy of the first embodiment.

[0011] This specification includes the disclosure of Japanese Patent Application No. 2022-075773, which is the priority basis of this application. All publications, patents, and patent applications cited in this specification are incorporated herein by reference in their entirety. Effect of the Invention

[0012] The present invention can provide an alloy that has high hardness and high crack resistance at high temperatures, a powder made of this alloy, and an alloy part and a composite part containing this alloy. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an example of a composite member according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates an example of a composite member according to one embodiment. [Diagram 3] FIG. 3 shows X-ray diffraction (XRD) patterns of the alloys of Examples 1-4. [Figure 4] FIG. 4 is an optical microscope image of the alloy of Example 1. [Diagram 5] FIG. 5 is an optical microscope image of the alloy of Example 2. [Figure 6]FIG. 6 is an optical microscope image of the alloy of Example 3. [Figure 7] FIG. 7 is an optical microscope image of the alloy of Example 4. [Figure 8] FIG. 8 is an optical microscope image of the alloy of the comparative example. [Figure 9] FIG. 9 is a scanning electron microscope (SEM) image of the continuous phase of the alloy of Example 1. [Figure 10] FIG. 10 is an SEM image of the alloy of Example 1. [Figure 11] FIG. 11 is an SEM image of the alloy of Example 1. [Figure 12] FIG. 12 is an SEM image of the alloy of Example 2. [Figure 13] FIG. 13 is an SEM image of the alloy of Example 2. [Figure 14] FIG. 14 is an SEM image of the alloy of Example 3. [Figure 15] FIG. 15 is an SEM image of the alloy of Example 3. [Figure 16] FIG. 16 is an SEM image of the alloy of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an alloy according to one embodiment of the present invention, and an alloy member, an alloy powder, and a composite member each containing the alloy will be described.

[0015] In this specification, a numerical range expressed using the symbol "~" includes the numerical values ​​written before and after "~" as the lower and upper limits. The upper and lower limits written before and after "~" can be combined in any combination. In addition, % indicating the content of a metal element means % by mass.

[0016] <Alloy> The alloy according to the embodiment (Ni-based alloy) contains at least one of Ni, Cr, C, Ti, Nb, and Ta as essential components. The alloy according to the embodiment may contain B, Al, Mo, and W as optional components. The alloy according to the embodiment contains, in mass%, 10 to 20% Cr, 1.0 to 2.5% C, 3 to 8% Ti, 8 to 15% in total of at least one of Nb and Ta, less than 0.5% B, 2% or less Al, 8% or less Mo, and 8% or less W, with the balance being Ni and unavoidable impurities. When the alloy according to the embodiment contains Mo and W, the total amount is less than 10%. In addition, the alloy according to the embodiment has a ratio of the total number of Ti, Nb, and Ta atoms to the number of C atoms exceeding 1.5. Since B, Al, Mo, and W are optional components, the lower limit of the amount of these in the alloy is 0%.

[0017] The chemical composition of the alloy can be analyzed by energy dispersive X-ray spectroscopy (EDX), inductively coupled plasma (ICP) emission spectrometry, or the like.

[0018] The components and their contents of the alloy according to the embodiment will be described in detail below.

[0019] (Cr:10~20%) Cr has the effect of forming a dense oxide film to improve the oxidation resistance of the alloy. A Cr content of 10% or more can provide a sufficient effect of improving oxidation resistance. If the Cr content exceeds 20%, eutectic Cr carbides and / or brittle intermetallic compounds are formed, decreasing the crack resistance. From the viewpoint of oxidation resistance and crack resistance, the Cr content is preferably 10 to 15%, more preferably 10 to 12%.

[0020] (C: 1.0~2.5%) C improves the wear resistance of the alloy by forming a carbide phase in the alloy, which will be described later. When the C content is 1.0% or more, a sufficient effect of improving wear resistance can be obtained. When the C content exceeds 2.5%, excessive carbides are formed at high temperatures, making it difficult to manufacture powder by the atomization method. From the viewpoints of wear resistance and ease of atomization, the C content is preferably 1.0 to 2.0%, and more preferably 1.0 to 1.5%.

[0021] (Ti: 3-8%) Ti forms a γ' phase (preferably γ' and γ'' phases) in the alloy, which will be described later, to improve the hardness of the alloy at high temperatures. In addition, Ti has a low free energy of carbide formation, so that a fine carbide phase is formed, thereby improving the wear resistance of the alloy without impairing the cracking resistance. When the Ti content is 3% or more, the γ' phase (preferably γ' and γ'' phases) and the carbide phase can be sufficiently formed. When the Ti content exceeds 8%, Ti is oxidized to form TiO2 during the additive manufacturing process, and melting defects due to TiO2 are likely to occur. When melting defects occur, they may become the starting point for cracks during cooling after molding. From the viewpoint of further improving the hardness at high temperatures, the Ti content is preferably 4 to 8%, more preferably 5 to 8%, and even more preferably 6 to 8%.

[0022] (Nb and / or Ta: 8~15%) Nb and Ta are elements of the same group in the periodic table and have very similar properties. Nb and Ta form the γ' phase (preferably the γ' phase and γ'' phase) to improve the hardness of the alloy at high temperatures, and also form a fine carbide phase, thereby improving the wear resistance of the alloy without impairing its cracking resistance. In other words, Nb and Ta can exert the same effects as Ti.

[0023] However, since Nb and Ta have a larger free energy of carbide formation than Ti, the effect of refining the carbide phase is smaller than that of Ti. On the other hand, Nb and Ta are less likely to oxidize than Ti, and are less likely to cause cracks during molding. In consideration of this point, the upper limit of the total content of Nb and Ta is higher than the upper limit of the content of Ti. By having a total content of either or both of Nb and Ta of 8% or more, it is possible to sufficiently form a γ' phase (preferably a γ' phase and a γ'' phase) and a carbide phase. If the total content of either or both of Nb and Ta exceeds 15%, Nb and / or Ta will form oxides during the additive manufacturing process, and melting defects due to the oxides will easily occur. The total content of at least one of Nb and Ta is preferably 9 to 13%, more preferably 10 to 12%, in consideration of hardness and wear resistance at high temperatures.

[0024] (The ratio of the total number of Ti, Nb and Ta atoms to the number of C atoms: more than 1.5) The ratio of the total number of Ti, Nb and Ta atoms to the number of C atoms contained in the alloy is more than 1.5. That is, (Ti+Nb+Ta) / C>1.5 (wherein Ti, Nb, Ta and C represent the number of atoms of each element contained in the alloy) is satisfied. When (Ti+Nb+Ta) / C is 1.5 or less, Ti, Nb and Ta are consumed in the formation of carbides and the γ' phase is not sufficiently formed. (Ti+Nb+Ta) / C is preferably more than 1.5 and less than 2.5, more preferably more than 1.5 and less than 2.4. Ti, Nb and Ta form fine particles of the γ' phase, and also form carbide particles to contribute to improving wear resistance. The amount of Ti, Nb and Ta and C is specified by the ratio of the number of atoms because Ti, Nb and Ta form carbides with a NaCl type crystal structure, and the carbides contain metal atoms and carbon atoms in a number ratio of 1:1.

[0025] (Al: 2% or less) Al promotes the formation of the γ' phase, or the γ' and γ'' phases, thereby improving the hardness of the alloy at high temperatures. If the Al content exceeds 2%, aging treatment after solution treatment becomes necessary to form the γ' phase, or the γ' and γ'' phases, and the time and energy required to manufacture the alloy increase. From the viewpoint of promoting the formation of the γ' phase, or the γ' and γ'' phases, the Al content is preferably 0.1 to 2%.

[0026] (Mo: 8% or less, W: 8% or less, total of Mo and W: less than 10%) Mo and W have a larger atomic radius than Ni, and can be dissolved in the continuous phase (matrix) described below to strengthen the alloy. Mo and W are elements of the same group in the periodic table, and in addition to having similar carbide formation free energies, the crystal structures of the carbides are the same. Therefore, Mo and W can be used interchangeably, and both Mo and W can be used. However, the total content of Mo and W is less than 10%. If the Mo content exceeds 8%, the W content exceeds 8%, or the total content of Mo and W is 10% or more, a coarse carbide phase is formed, and the crack resistance of the alloy is reduced. From the viewpoint of crack resistance, the total content of Mo and W is preferably 0 to 5%. From the viewpoint of crack resistance and strength, the total content of Mo and W is more preferably 3 to 5%. More preferably, the W content is 3 to 5% and Mo is substantially not contained.

[0027] (B: Less than 0.5%) B can be further added to the alloy according to the embodiment. It is believed that B contributes to improving the strength of the grain boundaries by improving the electronic structure of the grain boundaries. Therefore, when the alloy material contains B in the range of more than 0% and less than 0.5%, the mechanical properties of the alloy product in a high-temperature environment can be improved. In addition, when the B content is less than 0.5%, the generation of coarse precipitates in the alloy product can be suppressed, thereby suppressing the deterioration of the mechanical properties of the alloy product in a room temperature environment.

[0028] Furthermore, in this case, when forming a layered product (molded product) in an additive manufacturing process or when forming a molded product in another process, it is possible to suppress the occurrence of cracks in the molded product due to the inclusion of B. Also, if the B content is 0.5% or more, coarse particles may be formed, and not only the temperature but also the mechanical properties, especially the elongation, may decrease. For these reasons, it is preferable that B is less than 0.5%.

[0029] (Ni and unavoidable impurities) The alloy according to the embodiment is composed of Ni and inevitable impurities as the balance to the above-mentioned essential components and optional components. The alloy according to the embodiment is allowed to contain impurities contained in the raw materials and impurities derived from materials and manufacturing equipment. Specific examples of inevitable impurities include P, S, Sn, As, Pb, N, and O.

[0030] The content of each element of inevitable impurities is preferably 1% or less, more preferably 0.1% or less, even more preferably 0.01% or less, and particularly preferably below the detection limit. For example, the content of P is preferably 0.01% or less. The content of S is preferably 0.01% or less, more preferably 0.003% or less. The content of N is preferably 0.003% or less.

[0031] (Alloy structure) The alloy according to the embodiment has a face-centered cubic lattice structure and has a continuous phase (parent phase) including a γ phase and a γ' phase, and a carbide phase (dispersed phase) having a NaCl-type crystal structure dispersed in the continuous phase.

[0032] The continuous phase is preferably a phase mainly composed of a metal. Specifically, the continuous phase is preferably a phase containing at least one of Ni, Cr, Ti, Al, Nb, and Ta. The mass % of Ni in the continuous phase may be higher than the mass % of any other element contained in the continuous phase. Furthermore, the continuous phase has a face-centered cubic (FCC) structure, and preferably contains a γ phase and a γ' phase, and more preferably further contains a γ'' phase.

[0033] The γ phase is a phase in which the atoms constituting the FCC structure are randomly arranged at the vertices and face centers of the crystal lattice. On the other hand, the γ' phase and the γ'' phase are phases in which the atoms constituting the FCC structure are regularly arranged at the vertices and face centers of the crystal lattice, with the γ' phase having an L12 structure and the γ'' phase having a D022 structure, respectively. The γ' phase and the γ'' phase improve the hardness of the alloy at high temperatures. The average grain size of the γ' phase and the γ'' phase is 100 nm or less, preferably in the range of 10 to 100 nm. The average grain size of the γ' phase and the γ'' phase can be measured as follows.

[0034] A test piece with a thickness of about 100 nm is cut from the polished surface by the microsampling method using a focused ion beam (FIB), and this test piece is observed with a scanning transmission electron microscope (STEM) or a transmission electron microscope (TEM), or element mapping is performed by energy dispersive X-ray spectroscopy (EDX). Based on the obtained images, the average grain size of the γ' and γ'' phases is determined by calculating the arithmetic mean of the projected area circle equivalent diameters of 100 or more γ' and γ'' phases.

[0035] The carbide phase preferably has a NaCl type crystal structure. Carbide with a NaCl type crystal structure (MC carbide) is hard and can improve the wear resistance of the alloy. The carbide phase preferably has an average grain size of 50 μm or less, more preferably 0.5 to 50 μm, further preferably 1 to 30 μm, and particularly preferably 5 to 20 μm. When the carbide phase has a small grain size of 50 μm or less, the alloy can have high crack resistance. Furthermore, since fine carbides are dispersed in a continuous phase, voids generated in the cracked portion of the carbide are less likely to connect with each other compared to the case where coarse carbides are present, and as a result, it is expected that the effect of cracks in the entire alloy being less likely to propagate can be expected. The average grain size of the carbide phase can be measured by calculating the arithmetic mean of the diameter of the projected area circle equivalent of 100 or more carbide phases observed with a scanning electron microscope.

[0036] The alloy according to the embodiment has high hardness and high crack resistance at high temperatures, and is suitable for use as alloy powders used in additive manufacturing methods and as materials for alloy members used at high temperatures.

[0037] (Alloy form) The alloy according to the embodiment may have any form, such as an alloy ingot, an alloy member, or an alloy powder, so long as it has the above-mentioned chemical composition. The alloy according to the embodiment may be a part of a composite member. In addition, the alloy according to the present embodiment may be a cast product by die casting or the like, or a pressed product by direct rolling or the like, so long as it has the above-mentioned chemical composition.

[0038] The alloy ingot may be any of an ingot, a slab, a billet, etc. The shape of the alloy ingot may be a rectangular parallelepiped, a flat plate, a column, a rod, etc., and may have any appropriate shape and size depending on the application. For example, the alloy ingot may be produced by a general casting method in which an alloy is melted in a melting furnace, and then the molten metal is poured into a predetermined mold and solidified. As the melting furnace, a furnace that melts by converting electric energy into thermal energy, an electric resistance furnace that uses Joule heat, a low-frequency induction furnace that uses induced current, a high-frequency induction furnace that uses eddy current, etc. may be used.

[0039] <Alloy materials> The alloy member according to the present embodiment includes the alloy according to the above embodiment, and is preferably made of the alloy according to the above embodiment. The alloy member according to the present embodiment may be any of an additive manufacturing product, a casting, a pressing, a forging, etc., as long as it has the above chemical composition. The additive manufacturing product can be manufactured by an additive manufacturing method using an alloy powder as a material. The pressing product and the forging product can be manufactured by a method of processing and forming an alloy block and subjecting it to heat treatment, or a method of directly forming a molten metal and subjecting it to processing and heat treatment.

[0040] The use and shape of the alloy member according to the present embodiment are not particularly limited. The alloy member according to the present embodiment may be subjected to tempering such as aging treatment, appropriate heat treatment such as annealing, and / or appropriate processing such as cold working and hot working, depending on the use as a member and the required mechanical properties.

[0041] When the alloy member according to the present embodiment is manufactured as an additive manufacturing product, the entire alloy member may be manufactured by additive manufacturing, or only a part of the alloy member may be manufactured by additive manufacturing. That is, the alloy member according to the present embodiment includes a composite member in which a powder cladding (metal build-up) of an alloy having the above-mentioned chemical composition is applied to a base material of an alloy having the above-mentioned chemical composition.

[0042] The alloy part according to this embodiment may be a part that requires high hardness at high temperatures, and examples thereof include cutting tools, hot forging dies, screws for injection molding, cylinders for injection molding, drilling equipment for oil well plants, valves, joints, heat exchangers, and pumps for chemical plants, turbines for generators, impellers for compressors, and blades and disks for aircraft engines.

[0043] <Alloy powder> The alloy powder according to the present embodiment has the same chemical composition as the alloy according to the above embodiment. As long as the alloy powder according to the present embodiment has the above chemical composition, it can be made into a powder having an appropriate particle shape, appropriate particle size, and appropriate particle size distribution. The alloy powder according to the present embodiment is highly resistant to thermal stress during melting and solidification, and is therefore suitable as a material for additive manufacturing.

[0044] The alloy powder according to this embodiment may be composed only of alloy particles having the above-mentioned chemical composition, or may be a powder in which alloy particles having the above-mentioned chemical composition are mixed with particles having another chemical composition, or may be a powder in which the above-mentioned chemical composition is achieved by an aggregation of particles having any chemical composition.

[0045] In addition, the alloy powder according to the present embodiment may be manufactured by a mechanical manufacturing method such as mechanical pulverization or mechanical alloying, may be manufactured by a melting and solidifying process such as an atomizing method, or may be manufactured by a chemical manufacturing method such as an oxidation-reduction method or an electrolysis method. However, from the viewpoint of using the alloy powder in an additive manufacturing method, it is preferable to manufacture it by a melting and solidifying process because spherical particles are easily formed.

[0046] The alloy powder according to the present embodiment may be a granulated powder or a sintered powder. The granulated powder is a powder that is granulated so that at least some of the particles that make up the granular body are bonded to each other. The sintered powder is a powder that is sintered by heat treatment so that at least some of the particles that make up the granular body are bonded to each other.

[0047] From the viewpoint of appropriately adjusting the particle size distribution of the secondary particles, the sintered powder is preferably produced by a method in which the alloy powder is first granulated and then sintered. For example, the following method can be used to granulate the alloy powder and then sinter it to produce the granulated sintered powder.

[0048] First, for example, a powder of metal carbide and a powder containing the remaining chemical components that will form the above-mentioned chemical composition are prepared as raw materials. The prepared raw material powder is then wet-mixed with a binder. As the binder, it is preferable to use a hydrocarbon-based binder. Examples of the hydrocarbon-based binder include wax such as paraffin. When the mixture obtained by mixing is spray-dried with a spray dryer, a powder with an average particle diameter d 50 A granulated powder of the mixture having an average particle diameter d 50 means the particle size (median size) corresponding to an integrated value of 50 volume % in the volume-based particle size distribution measured by a laser diffraction scattering method.

[0049] Next, the granulated powder of the mixture is dried to remove the binder. The degreasing temperature may be set to a temperature at which the binder used can be sufficiently removed within a required time. The degreasing temperature may be set to, for example, 400 to 600°C. Then, the granulated powder of the mixture is subsequently fired after being degreased to sinter the particles together. The firing temperature depends on the chemical composition, but is set to, for example, 1000°C or higher. When the firing temperature is set to a high temperature of 1000°C or higher, the density of the sintered body increases, and therefore a sintered powder with a large bulk density suitable for improving the packing density can be obtained.

[0050] The fired sintered powder can be naturally cooled, for example, by air cooling, and then classified according to the purpose by sieve classification, dry classification, wet classification, or the like.

[0051] The metal carbide powder used as the raw material for the granulated powder has an average particle diameter of d 50 However, the powder containing the remaining chemical components has an average particle diameter d 50 However, the average particle diameter of the binder powder is preferably 0.1 to 50.0 μm, and more preferably 0.1 to 20.0 μm. 50 However, the thickness is preferably 0.1 to 1.0 μm.

[0052] When such raw materials are used, the particles are well bonded to each other, C is sufficiently dispersed, and the average particle diameter d 50 After the granulated powder is sintered to obtain a sintered powder, the average particle diameter d 50 By classifying the powder so that the particle size is 20 to 100 μm, it is possible to obtain alloy powder with a highly uniform particle size suitable for additive manufacturing processes.

[0053] By using the above-mentioned method of granulating the alloy powder and then sintering it to obtain a granulated sintered powder, the particles constituting the powder body can be sufficiently bonded together by sintering, while the binder used in the granulation operation can be reliably removed from the powder body. In general, if the degreased granulated powder is directly used in an additive manufacturing method using a directed energy deposition method, the granulated powder is easily crushed during supply to the modeling area. In contrast, in the case of a granulated sintered powder, the particles are firmly bonded together by sintering, so that crushing during additive manufacturing is suppressed, and defects and non-uniformity of the chemical composition during melting and solidification due to oxidation and the inclusion of impurities can be reduced.

[0054] The alloy powder may be subjected to a spheroidizing treatment before being used in additive manufacturing. As the spheroidizing treatment, the thermal plasma droplet refining (PDR) method, heat treatment at high temperature, etc. can be used. The PDR method is a method in which the powder is introduced into plasma and heat treated at high temperature. According to the PDR method, some or all of the particles constituting the powder or granular material are instantly melted and solidified, so that particles close to a perfect sphere can be obtained due to surface tension. The surface of the particles becomes smooth and the flowability of the powder or granular material is increased, so that the molding accuracy of the additive manufacturing object can be improved. In addition, defects during melting and solidification and defects in the solidification structure due to non-uniformity of the chemical composition can be reduced.

[0055] The alloy powder according to the present embodiment can be manufactured by various atomization methods. The atomization method is a method in which molten metal is dispersed as droplets by the kinetic energy of a medium sprayed at high pressure, and the droplets of the molten metal are solidified to produce powder particles. As the atomization method, any of water atomization, gas atomization, jet atomization, and the like can be used.

[0056] Water atomization is a method in which high-pressure water is sprayed as an atomizing medium onto molten metal that has been caused to flow down from the bottom of a tundish, etc., to produce metal powder using the kinetic energy of the water. Particles produced by water atomization tend to be amorphous. This is because water, the atomizing medium in water atomization, has a faster cooling rate than other atomization methods. However, particles produced by water atomization tend to have irregular shapes.

[0057] Gas atomization is a method for producing metal powder by spraying high-pressure nitrogen, inert gas such as argon, or high-pressure air as an atomizing medium onto molten metal flowing down from the bottom of a tundish. Particles produced by gas atomization tend to be spherical. This is because the inert gas and air used as the atomizing medium in gas atomization have a slower cooling rate than water atomization. The molten metal that has been turned into droplets by the atomizing medium remains in a liquid state for a relatively long period of time, and it is believed that the spheroidization proceeds due to surface tension.

[0058] Jet atomization is a method for producing metal powder by spraying a high-speed, high-temperature flame jet as an atomizing medium onto molten metal flowing down from the bottom of a tundish. A supersonic combustion flame generated by burning kerosene or the like is used as the flame jet. Therefore, the molten metal is accelerated for a relatively long period of time and becomes fine particles. Particles produced by the jet atomization method tend to be spherical and have a particle size distribution with a small average particle size.

[0059] From the viewpoint of use in additive manufacturing, the alloy powder according to this embodiment is preferably manufactured by gas atomization. Particles manufactured by gas atomization have high sphericity and high flowability as powder particles. This makes it possible to improve the molding accuracy of the layered manufactured object. In addition, defects during melting and solidification and defects in the solidified structure due to non-uniformity in chemical composition can be reduced.

[0060] (Additive Manufacturing) The alloy powder according to the present embodiment can be used in an appropriate additive manufacturing method. In general, additive manufacturing methods for metal materials are roughly divided into a Powder Bed Fusion (PBF) method and a Directed Energy Deposition (DED) method.

[0061] Powder Bed Fusion (PBF) is a method of forming a powder bed by spreading metal powder on a base material, and irradiating the metal powder spread in the target area with a beam to melt and solidify the metal powder to create a shape. In the PBF method, three-dimensional additive manufacturing is performed by repeating the lamination of the powder bed and the melting and solidification of the metal powder every time a two-dimensional model is performed on the powder bed.

[0062] There are two types of Powder Bed Fusion (PBF) methods: one that uses a laser beam as the heat source, and one that uses an electron beam as the heat source. The methods that use a laser beam are broadly divided into the Selective Laser Melting (SLM) method and the Selective Laser Sintering (SLS) method. The method that uses an electron beam is called the Selective Electron Beam Melting (SEBM) method, or simply EBM method.

[0063] The selective laser melting (SLM) method is a method of melting or sintering metal powder with a laser beam. The selective laser sintering (SLS) method is a method of sintering metal powder with a laser beam. In the SLM and SLS methods that use a laser beam, the metal powder is melted and solidified in an inert atmosphere such as nitrogen gas.

[0064] The electron beam powder melting (SEBM / EBM) method is a method to melt metal powder using an electron beam as a heat source. The EBM method using an electron beam is performed by irradiating metal powder with the electron beam and converting the kinetic energy into heat to melt the metal powder. In the EBM method, the irradiation of the electron beam and the melting and solidification of the metal powder are carried out under high vacuum.

[0065] Directed energy deposition (DED) is a method of supplying metal powder to a base material or an already-modeled region and irradiating it with a beam, melting and solidifying the metal powder supplied to the region. In the DED method, the supply of metal powder and the irradiation of the beam are scanned two-dimensionally or three-dimensionally, and the deposition of solidified metal on the already-modeled region is repeated, resulting in three-dimensional additive manufacturing.

[0066] The DED method is also called the metal deposition method. There are two types of DED methods: the Laser Metal Deposition (LMD) method, which uses a laser beam as the heat source, and a method that uses an electron beam as the heat source. Among the DED methods, the method of applying powder cladding to a base material using a laser beam is also called laser powder cladding welding.

[0067] Among the various additive manufacturing methods, the powder bed fusion (PBF) method has the advantage of high shape accuracy of the layered object. On the other hand, the directed energy deposition (DED) method has the advantage of high speed modeling. In particular, among the powder bed fusion (PBF) methods, the selective melting and solidification of metal powder is possible by irradiating a powder bed with a tiny laser beam diameter, with each layer being several tens of micrometers thick.

[0068] (Additive manufacturing conditions) The thickness of one layer during additive manufacturing can be, for example, 0.1 to 1.0 mm, and is preferably 0.4 to 0.5 mm. The thickness (distance from the interface between the substrate and the alloy to the surface of the first layer) of the alloy (including the diffusion layer formed near the interface between the substrate and the alloy) formed on the surface of the substrate (base plate) is 0.1 to 1 mm, and the total thickness of the alloy (including the diffusion layer near the interface) is 0.1 to 2 mm. The beam diameter of the laser is preferably about 3 mm at the irradiation position. The laser output is preferably 1500 to 2400 W. The laser scanning speed is preferably 500 to 1000 mm / min. The powder supply amount is preferably 5 to 15 g / min.

[0069] If the heat input E, which is the density of the energy input by laser irradiation to rapidly melt the raw material powder, is too small, the defect rate will increase and, furthermore, the supplied powder will not melt, making it difficult to maintain the shape of the molded object. On the other hand, if the heat input E is too large, a wide area of ​​the base plate or molded object centered on the laser irradiation position will melt, making it difficult to maintain the shape of the molded object. The heat input E (J / mm) can be calculated from formula (1) using the laser output P (W) and the laser scanning speed v (mm / min).

[0070] E = (P / v) × 60 (1)

[0071] When using the directed energy deposition (DED) method among additive manufacturing methods, the following are preferable: laser output: 1500-2400 W, heat input: 100-5000 J / mm (1-50 kJ / cm), powder supply amount: 0.1-1 g / cm, powder heat input: 5-100 kJ / g. Furthermore, the carrier gas flow rate: 1-50 L / mm, and shield gas flow rate: 1-50 L / min are preferable.

[0072] (Particle size distribution of alloy powder) The alloy powder according to the present embodiment has an average particle diameter (median diameter) d corresponding to an integrated value of 50 volume % in a volume-based particle size distribution measured by a laser diffraction scattering method. 50(Hereinafter, as appropriate, "average particle diameter d 50 It is preferable that the average particle diameter d is in the range of 5 to 500 μm. In additive manufacturing, melting and solidification proceeds for each group of powder. If the particle diameter of the alloy powder is too small, the beads will also be small, and defects such as bead interface failure will easily occur. On the other hand, if the particle diameter of the alloy powder is too large, the beads will also be large, and defects due to uneven cooling rate will easily occur. However, 50 If the thickness is within the range of 5 to 500 μm, a layered object with few defects can be easily obtained.

[0073] However, the optimal particle size and particle size distribution of the alloy powder differ depending on the additive manufacturing method. Therefore, it is preferable to adjust the particle size and particle size distribution of the alloy powder according to the additive manufacturing method. From the viewpoint of using the alloy powder according to the present embodiment in the powder bed fusion (PBF) method or the directed energy deposition (DED) method, the average particle size d 50 The thickness is preferably within the range of 10 to 250 μm, and more preferably within the range of 20 to 150 μm.

[0074] For example, in the selective powder melting (SLM) method, the average particle diameter d 50 is preferably 10 to 60 μm, more preferably 20 to 40 μm. In addition, the particle diameter d corresponding to an integrated value of 10% by volume in the volume-based particle size distribution measured by a laser diffraction scattering method is 10 (Hereinafter, "particle diameter d" will be used as appropriate) 10 ") is preferably 5 to 35 μm. In addition, the particle diameter d corresponding to an integrated value of 90 volume % in the volume-based particle size distribution measured by a laser diffraction scattering method is 90 (Hereinafter, "particle diameter d" will be used as appropriate) 90 ") is preferably 20 to 100 μm.

[0075] In the SLM method, if the particle size of the metal powder is less than 10 μm, the powder will have poor storability and spreadability as a granular material, and the powder layered as a powder bed will tend to be unevenly distributed. Also, if the particle size exceeds 100 μm, the beam will tend to melt the powder incompletely, causing defects in the solidified structure and increasing surface roughness. However, with the above particle size distribution, it is easy to form a powder bed with a flat and uniform thickness, and it is also easy to repeatedly layer the powder bed, making it easier to obtain an additive manufacturing body with fewer defects.

[0076] In addition, in the laser metal deposition (LMD) method or powder bed type electron beam melting (EBM) method, the average particle diameter d 50 is preferably 30 to 250 μm, more preferably 60 to 120 μm. 10 is preferably 15 to 100 μm. 90 is preferably 50 to 500 μm.

[0077] In the LMD method, if the average particle size of the metal powder is small, the flow of the powder transported to the nozzle head is easily biased, making it difficult to stably supply the metal powder to the molten pool. Also, if the particle size exceeds about 500 μm, the metal powder may cause blockages in the nozzle head, melting may be incomplete, defects may occur in the solidification structure, and the surface roughness may increase. On the other hand, in the EBM method, if the average particle size of the metal powder is small, the smoke phenomenon is likely to occur. However, with the above particle size distribution, the supply of the metal powder to the molten pool and the non-scattering properties of the metal powder are good, making it easier to obtain a highly accurate additive manufacturing object.

[0078] <Composite materials> The composite member according to the present embodiment is obtained by integrating an alloy member having the above-mentioned chemical composition or an alloy layer formed from an alloy powder having the above-mentioned chemical composition with another member. Examples of the integration method include welding, soldering, brazing, mechanical bonding, and diffusion bonding.

[0079] Fig. 1 is a cross-sectional view showing a schematic example of a composite member according to the present embodiment. The composite member 10 shown in Fig. 1 has a substrate 2 and an alloy layer 1 laminated on the surface of the substrate 2. Such a composite member 10 can be manufactured by a directed energy deposition (DED) additive manufacturing method using an alloy powder.

[0080] The alloy layer 1 includes the alloy according to the embodiment, and is preferably made of the alloy according to the embodiment. The shape and dimensions of the alloy layer 1 are not particularly limited. In the example shown in Fig. 1, the alloy layer 1 is a columnar layer formed by powder deposition on the surface of the base material 2, but the alloy layer 1 may be a thin film coating that covers the surface of the base material 2, or an additive manufacturing body having any three-dimensional shape.

[0081] The shape and material of the substrate 2 are not particularly limited. For example, an Fe-based alloy or a Ni-based alloy can be used as the substrate 2. Conventionally, in additive manufacturing, the substrate was preheated to reduce thermal stress in order to prevent cracks caused by thermal stress resulting from melting and solidification of the raw material powder. Therefore, the conventional substrate had to have high heat resistance. However, since the alloy layer 1 of the composite member 10 according to the present embodiment has high crack resistance, preheating of the substrate 2 is not necessary or the preheating temperature of the substrate 2 can be reduced. Therefore, the substrate 2 of the composite member 10 according to the present embodiment does not have to have high heat resistance.

[0082] A mixed layer 3 may be formed between the substrate 2 and the alloy layer 1. The mixed layer 3 has an intermediate chemical composition between the substrate 2 and the alloy layer 1. The mixed layer 3 is formed by the diffusion of atoms of the substrate 2 and the alloy layer 1 when the raw material powder is melted and solidified in the additive manufacturing method.

[0083] As shown in FIG. 2, the composite material 10 may further have a coating layer 4 formed on the surface of the alloy layer 1. The coating layer 4 can be formed by, for example, a method of nitriding the surface of the alloy layer 1, a chemical vapor deposition (CVD) method, or a physical vapor deposition (PVD) method. The material of the coating layer 4 is not particularly limited, but is preferably, for example, titanium carbide (TiC), titanium nitride (TiN), titanium carbonitride (TiCN), aluminum oxide (Al2O3), titanium aluminum nitride (TiAlN), or chromium nitride (CrN). By forming the coating layer 4 on the surface of the alloy layer 1, the wear resistance of the composite material 10 can be improved.

[0084] The composite member according to the embodiment may be a member that requires high hardness at high temperatures, similar to the alloy member described above, and examples thereof include cutting tools, hot forging dies, screws for injection molding, cylinders for injection molding, drilling equipment for oil well plants, valves, joints, heat exchangers, and pumps for chemical plants, turbines for generators, impellers for compressors, and blades and disks for aircraft engines. Also included in the composite member according to the embodiment are dies that have been powder-laid for die repair.

[0085] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and various modifications are possible within the scope of the present invention. For example, the present invention is not necessarily limited to having all the configurations of the above embodiment. It is possible to replace a part of the configuration of a certain embodiment with another configuration, add a part of the configuration of a certain embodiment to another form, or omit a part of the configuration of a certain embodiment. EXAMPLES

[0086] The present invention will be described in detail below with reference to examples, but the technical scope of the present invention is not limited to these examples.

[0087] (1) Preparation of alloy ingot Examples 1 to 4 The following alloy raw materials were prepared and weighed to obtain the chemical compositions shown in Table 1. Cr: Powder with particle size of 63 to 90 μm Ti: 1-3mm crushed particles Nb: 3-5mm crushed particles W: Powder with particle size of 50 μm or less C: Spherical particles with a diameter of 1 to 2 mm Al: Spherical particles with diameter of 5 to 10 mm Ni: Spherical particles with diameters of 8 to 15 mm

[0088] [Table 1]

[0089] The weighed raw materials were mixed in an alumina crucible, melted in a high-frequency induction melting furnace, and poured into a water-cooled copper mold to obtain an alloy ingot.

[0090] Comparative Example Test pieces were prepared by forming a WC-Co superalloy body on a Ni-based alloy substrate by additive manufacturing using WC-Co cemented carbide powder containing 40% Co and the remainder WC as the raw material. Additive manufacturing was performed by depositing the raw material to a height of 10 mm with 8 passes per layer using a directed energy deposition laser deposition method, stacking about 20 layers. The composition of the Ni-based alloy substrate used and the additive manufacturing conditions were as follows. The additive manufacturing conditions were set so that the heat input to the raw material powder was relatively small so that cracks were unlikely to occur between the substrate and the molded body.

[0091] Composition of Ni-based alloy substrate C: 0.03% Si: 0.08% Mn: 0.05% P: 0.004% S: 0.0002% Cr: 18.58% Mo: 3.08% Co: 0.04% Cu: 0.02% Al: 0.56% Ti: 0.94% Fe: 24.19% B: 0.0038% Ni: remaining

[0092] Additive Manufacturing Conditions Laser power: 1200W Laser beam scanning speed: 100 mm / min Heat input: 7.2kJ / cm Powder supply amount: 0.2g / cm Powder heat input: 36kJ / g Defocus distance: 20mm Carrier gas flow rate: 5.5L / mm Shielding gas flow rate: 20L / min Side gas flow rate: 10L / min

[0093] (2) Elemental analysis The alloy ingots of each example were subjected to elemental analysis by ICP emission spectrometry. In addition, the ratio of the total number of Ti, Nb, and Ta atoms to the number of C atoms ((Ti+Nb+Ta) / C) was calculated from the elemental analysis results. The results are shown in Table 2.

[0094] [Table 2]

[0095] (3) Crystal structure analysis Test pieces of a prescribed shape were cut out from the alloy ingot of each example, polished with waterproof emery paper up to No. 1000, and subjected to XRD measurement under the following conditions. The results are shown in FIG. Source: Cu Tube voltage: 48kV Tube current: 28mA Sampling interval: 0.02° Scanning range: 2θ=20°~100°

[0096] In each example, a main peak assigned to the FCC structure and a peak assigned to NaCl-type carbide were confirmed.

[0097] (4) Microstructural observation Specimens of a given shape were cut out from the alloy ingot of each example and the WC-Co superalloy shaped body of the comparative example, and observed with an optical microscope and a scanning electron microscope (SEM). Figures 4 to 7 show optical microscope images of the alloys of Examples 1 to 4, respectively. Figure 8 shows an optical microscope image of the alloy of the comparative example. Figures 10 to 16 show SEM images of the alloys of Examples 1 to 4.

[0098] As shown in Figs. 4 to 7 and Figs. 10 to 16, the alloys of Examples 1 to 4 had a continuous phase 11 (light colored part) and a carbide phase 12 (dark colored part) dispersed in the continuous phase 11. Considering the above-mentioned XRD measurement results, it is estimated that the continuous phase 11 has an FCC structure and the carbide phase 12 has an NaCl structure. The circle equivalent diameter of the carbide phase 12 of the alloys of Examples 1 to 4 was 50 μm or less, which was smaller than the average circle equivalent diameter of the carbide phase 22 (dark colored part in Fig. 8) of the WC-Co cemented carbide of the comparative example. In addition, in the observation image of the continuous phase 11 of the alloys of Examples 1 to 4 at a higher magnification (see Fig. 9), a white granular structure with a circle equivalent diameter of 10 to 20 nm was present, suggesting that the continuous phase 11 contains a γ phase and a γ' phase.

[0099] (5) High temperature hardness evaluation A test piece of a given shape was cut out from the alloy block of each example, and the hardness at 700°C was measured. Specifically, a high-temperature micro Vickers hardness tester (AVK-HF) manufactured by Mitutoyo Corporation was used to press a diamond indenter into the test piece heated to 700°C with a load of 5 kgf for 30 seconds, and the diagonal length of the indentation was measured. The measurement was performed 10 times, and the hardness of the alloy of each example was calculated from the average value of 8 measured values ​​excluding the maximum and minimum values. In the same manner, the hardness at 700°C of the WC-Co superalloy of the comparative example was measured. The results are shown in Table 3.

[0100] [Table 3]

[0101] It was confirmed that all of the alloys of Examples 1 to 4 had a higher hardness at 700°C than the WC-Co cemented carbide shaped body of the comparative example.

[0102] (6) Crack resistance evaluation A test piece of a predetermined shape was cut out from the alloy ingot of each Example. Each test piece was irradiated with a laser beam under the following conditions, and each test piece was melted and solidified. A test piece of the comparative example was also irradiated with a laser beam in the same manner, and was melted and solidified.

[0103] Laser light irradiation conditions Laser light irradiation device: 2kW fiber laser Laser light output: 1600W Shielding gas: Ar Laser light incidence angle: 10° Laser beam scanning width: 13mm Laser beam scanning speed: 500 mm / min

[0104] Next, the presence or absence of cracks in each test piece after cooling was evaluated by a penetrant test. None of the test pieces of Examples 1 to 4 had any cracks. On the other hand, cracks were confirmed in the test piece of the Comparative Example. This result shows that the alloys of Examples 1 to 4 are less likely to crack due to thermal stress during melting and solidification. This suggests that the alloys of Examples 1 to 4 have high resistance to thermal stress in additive manufacturing and are less likely to crack. One of the factors that led to high crack resistance in Examples 1 to 4 is thought to be the formation of finer carbide phases in Examples 1 to 4 compared to the Comparative Example. [Explanation of symbols]

[0105] 1 alloy layer, 2 substrate, 3 mixed layer, 4 coating layer, 10 composite member

Claims

1. In mass percent, Cr 10-20%, C 1.0 to 2.5%, Ti: 3-8% Nb and / or Ta, 8 to 15% in total; B is less than 0.5%; Al is 2% or less, Mo: 8% or less Contains 8% or less W; The sum of Mo and W is less than 10%; The balance is Ni and unavoidable impurities, An alloy having a ratio of the total number of Ti, Nb and Ta atoms to the number of C atoms greater than 1.

5.

2. a continuous phase having a face-centered cubic lattice structure and including a γ phase and a γ′ phase; a carbide phase having a NaCl-type crystal structure dispersed in the continuous phase; 2. The alloy of claim 1 having the formula:

3. The alloy of claim 2, wherein the average grain size of said carbide phase is less than or equal to 50 μm.

4. In mass percent, Cr 10-20%, C 1.0 to 2.5%, Ti: 3-8% Nb and / or Ta, 8 to 15% in total; B is less than 0.5%; Al is 2% or less, Mo: 8% or less Contains 8% or less W; The sum of Mo and W is less than 10%; The balance is Ni and unavoidable impurities, An alloy powder in which the ratio of the total number of Ti, Nb and Ta atoms to the number of C atoms is greater than 1.

5.

5. The alloy powder according to claim 4, which is a granulated and sintered powder.

6. The average particle diameter d corresponding to an integrated value of 50 volume % in the volume-based particle size distribution measured by a laser diffraction scattering method 50 The alloy powder according to claim 4 or 5, wherein the average particle size is 5 to 500 μm.

7. An alloy member comprising at least a part of the alloy according to any one of claims 1 to 3.

8. A substrate and a laminated alloy layer on a surface of the substrate, A composite component, wherein the laminated alloy layer comprises the alloy of any one of claims 1 to 3.

9. A substrate and a laminated alloy layer on a surface of the substrate, A mold, wherein the laminated alloy layer comprises the alloy of any one of claims 1 to 3.

Citation Information

Patent Citations

  • Nickel-based directional high-temperature alloy laser directional additive manufacturing method

    CN107774997A

  • Metal powder consisting of spherical particle

    JP2016194143A

  • Manufacturing method of cemented carbide cutting tool and cutting tool manufactured by this method

    JP2017501890A

  • Ni-BASED SUPER ALLOY

    JP2019131856A

  • Ni-based alloy member comprising additively manufactured article, method for manufacturing ni-based alloy member, and product using ni-based alloy member

    WO2020179766A1